A cost comparison study to review community versus acute hospital models of nursing care delivered to oncology patients. (December 2020) - O'Mahony, Cian; Murphy, Kevin D.; O'Brien, Gary L.; Aherne, Joe; Hanan, Terry; Mullen, Louise; Keane, Maccon; Donnellan, Paul; Davey, Claire; Browne, Helen; Malee, Kathleen; Byrne, Stephen
Abstract: Purpose: Ireland's Sláintecare health plan is placing an increased focus on primary care. A community oncology nursing programme was developed to train community nurses to deliver care in the community. While the initial pilot was proven to be clinically safe, no cost evaluation was carried out. This study aims to compare the costs of providing cancer support services in a day-ward versus in the community. Methods: 183 interventions (40 in day-ward and 143 in community) were timed and costed using healthcare professional salaries and the Human Capital method. Results: From the healthcare provider perspective, the day-ward was a significantly cheaper option by an average of €17.13 (95% CI €13.72 - €20.54, p < 0.001). From the societal perspective, the community option was cheaper by an average of €2.77 (95% CI -€3.02 – €8.55), although this was a non-significant finding. Sensitivity analyses indicate that the community service may be significantly cheaper from the societal perspective. Conclusions: Given the demand for cost-viable options for primary care services, this programme may represent a national option for cancer care in Ireland when viewed from the societal perspective. Highlights: The Community Oncology Nursing Programme is a safe method of delivering care. A cost-comparison of day-ward versus community care for cancer support services was carried out. Community oncology nursing care in Ireland may be a cost-viable option from societal perspective. Ireland's focus on primary care options means this programme may be rolled out nationally.